Protocol for developing a core outcome set for male infertility research: an international consensus development study. Issue 2 (16th March 2022) - Rimmer, Michael P; Howie, Ruth A; Anderson, Richard A; Barratt, Christopher L R; Barnhart, Kurt T; Beebeejaun, Yusuf; Bertolla, Ricardo Pimenta; Bhattacharya, Siladitya; Björndahl, Lars; Bortoletto, Pietro; Brannigan, Robert E; Cantineau, Astrid E P; et al.
Abstract: STUDY QUESTION: We aim to develop, disseminate and implement a minimum data set, known as a core outcome set, for future male infertility research. WHAT IS KNOWN ALREADY: Research into male infertility can be challenging to design, conduct and report. Evidence from randomized trials can be difficult to interpret and of limited ability to inform clinical practice for numerous reasons. These may include complex issues, such as variation in outcome measures and outcome reporting bias, as well as failure to consider the perspectives of men and their partners with lived experience of fertility problems. Previously, the Core Outcome Measure for Infertility Trials (COMMIT) initiative, an international consortium of researchers, healthcare professionals and people with fertility problems, has developed a core outcome set for general infertility research. Now, a bespoke core outcome set for male infertility is required to address the unique challenges pertinent to male infertility research. STUDY DESIGN, SIZE, DURATION: Stakeholders, including healthcare professionals, allied healthcare professionals, scientists, researchers and people with fertility problems, will be invited to participate. Formal consensus science methods will be used, including the modified Delphi method, modified Nominal Group Technique and the National Institutes of Health's consensus development conference. PARTICIPANTS/MATERIALS, SETTING, METHODS: An international steering group, including the relevant stakeholders outlined above, has been established to guide the development of this core outcome set. Possible core outcomes will be identified by undertaking a systematic review of randomized controlled trials evaluating potential treatments for male factor infertility. These outcomes will be entered into a modified Delphi method. Repeated reflection and re-scoring should promote convergence towards consensus outcomes, which will be prioritized during a consensus development meeting to identify a final core outcome set. We will establish standardized definitions and recommend high-quality measurement instruments for individual core outcomes. STUDY FUNDING/COMPETING INTEREST(S): This work has been supported by the Urology Foundation small project award, 2021. C.L.R.B. is the recipient of a BMGF grant and received consultancy fees from Exscentia and Exceed sperm testing, paid to the University of Dundee and speaking fees or honoraria paid personally by Ferring, Copper Surgical and RBMO. S.B. received royalties from Cambridge University Press, Speaker honoraria for Obstetrical and Gynaecological Society of Singapore, Merk SMART Masterclass and Merk FERRING Forum, paid to the University of Aberdeen. Payment for leadership roles within NHS Grampian, previously paid to self, now paid to University of Aberdeen. An Honorarium is received as Editor in Chief of Human Reproduction Open. M.L.E. is an advisor to the companies Hannah and Ro. B.W.M. received an investigator grant from the NHMRC, No: GNT1176437 is a paid consultant for ObsEva and has received research funding from Ferring and Merck. R.R.H. received royalties from Elsevier for a book, consultancy fees from Glyciome, and presentation fees from GryNumber Health and Aytu Bioscience. Aytu Bioscience also funded MiOXYS systems and sensors. Attendance at Fertility 2020 and Roadshow South Africa by Ralf Henkel was funded by LogixX Pharma Ltd. R.R.H. is also Editor in Chief of Andrologia and has been an employee of LogixX Pharma Ltd. since 2020. M.S.K. is an associate editor with Human Reproduction Open . K.Mc.E. received an honoraria for lectures from Bayer and Pharmasure in 2019 and payment for an ESHRE grant review in 2019. His attendance at ESHRE 2019 and AUA 2019 was sponsored by Pharmasure and Bayer, respectively. The remaining authors declare no competing interests. TRIAL REGISTRATION NUMBER: Core Outcome Measures in Effectiveness Trials (COMET) initiative registration No: 1586. Available at www.comet-initiative.org/Studies/Details/1586 . TRIAL REGISTRATION DATE: N/A. DATE OF FIRST PATIENT'S ENROLMENT: N/A.